Enhanced Contour Description for People Detection in Images - Du, Xiaoyun (Université d'Ottawa / University of Ottawa, 2014)
People detection has been an attractive technology in computer vision. There are many useful applications in our daily life, for instance, intelligent surveillance and driver assistance system. People detection is a challenging matter as people adopt a wide range of poses, wear diverse clothes, and are visible in different kind of backgrounds with significant changes in illumination. In this thesis, some advanced techniques and powerful tools are presented in order to design a robust people detection system. First a baseline model is implemented by combining the Histogram of Oriented Gradients descriptor and linear Support Vector Machines. This baseline model obtains a good performance on the well-known INRIA dataset. Second an advanced model is proposed which has a two-layer cascade framework that achieves both accurate detection and lower computational complexity. For the first layer, the baseline model is used as a filter to generate several candidates. In this procedure, most positive samples survived and the majority of negative samples are rejected according to a preset threshold. The second layer uses a more discriminative model. We combine the Variational Local Binary Patterns descriptor, and the Histogram of Oriented Gradients descriptor as a new discriminative feature. Furthermore multi-scale feature descriptors are used to improve the discriminative power of the Variational Local Binary Patterns feature. Then we perform Feature Selection using the Feature Generating Machine in order to generate a concise descriptor based on this concatenated feature. Moreover Histogram Intersection Kernel Support Vector Machines is employed as an efficient tool of classification. The bootstrapping algorithm is used in the training procedure to exploit the information of the dataset. Finally our approach has a good performance on the INRIA dataset, with results superior to the baseline model.
Keywords: People Detection; Variational LBP; Feature selection; Intersection kernel; Bootstrapping